2017
DOI: 10.1021/acs.jproteome.6b00948
|View full text |Cite
|
Sign up to set email alerts
|

Combined Peptidomic and Proteomic Analysis of Electrically Stimulated and Manually Dissected Venom from the South American Bullet Ant Paraponera clavata

Abstract: Ants have evolved venoms rich in peptides and proteins used for predation, defense, and communication. However, they remain extremely understudied due to the minimal amount of venom secreted by each ant. The present study investigated the differences in the proteome and peptidome of the venom from the bullet ant, Paraponera clavata. Venom samples were collected from a single colony either by manual venom gland dissection or by electrical stimulation and were compared using proteomic methods. Venom proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 79 publications
5
28
0
Order By: Relevance
“…This is the first characterization of the venom proteins of P. striata . Our data show that the venom of P. striata is highly diverse, similar to the venom of other ants that have been characterized (Aili et al., , ; Bouzid et al., ; Touchard et al., ). The combination of the three fractionation and analysis methods allowed the identification of 43 proteins in the venom of P. striata .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is the first characterization of the venom proteins of P. striata . Our data show that the venom of P. striata is highly diverse, similar to the venom of other ants that have been characterized (Aili et al., , ; Bouzid et al., ; Touchard et al., ). The combination of the three fractionation and analysis methods allowed the identification of 43 proteins in the venom of P. striata .…”
Section: Discussionsupporting
confidence: 74%
“…Ants employ venoms for a variety of purposes including predation and defense against predators and competitors, defense against microbial pathogens, social communication (Orivel & Dejean, ; Touchard et al., ), and as herbicides (Touchard et al., ). However, ant venoms remain almost unexplored in comparison with other animals (Aili et al., ; Rifflet et al., ; Touchard et al., ). The species of ants with the most well‐characterized venoms are the fire ant Solenopsis invicta and Solenopsis saevissima and Myrmecia pilosula (Santos et al., ; Touchard et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the investigation of ant venoms was greatly limited by the difficulty in gathering large amounts of venom due to the small size of these insects. However, the use of new techniques to collect venoms now permits large amounts of ant venom to be quickly obtained [12,13]. Furthermore, the use of multi-omics strategies to study ant venoms recently revealed the whole peptidome of three ant species belonging to the subfamilies Ponerinae, Myrmicinae, and Myrmeciinae, allowing a high-throughput identification of novel peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing only the protein portion of the P. paulista venom also show variation in the chemical composition between different colonies (Dias et al, 2014), as well as studies with ants that found variation in the venom composition of colonies of the same population (Aili et al, 2017), in which the authors suggested genetic polymorphism or small environmental variations between areas.…”
Section: Discussionmentioning
confidence: 99%